Pengaruh Kualitas Sistem, Kualitas Informasi Dan Kualitas Layanan Terhadap Kepuasan Pengguna Aplikasi Sibisa Di Instansi Dinas Kependudukan Dan Pencatatan Sipil Kota Medan - tridayanthi, khori ayu (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2024)
This research aims to determine the influence of system quality, information quality and service quality on user satisfaction of the Sibisa application at the Medan City Population and Civil Registration Service agency. This research was conducted using a quantitative approach. The data collection technique in this research uses a questionnaire distribution technique. The types of data used are primary and secondary data as research data sources. Based on analysis tests, the research results show that: 1) System quality variables have no effect on user satisfaction of the Sibisa application at the Medan City Population and Civil Registration Service Agency. 2) The information quality variable has no effect on user satisfaction of the Sibisa application at the Medan City Population and Civil Registration Service Agency. 3) The service quality variable has a significant effect on user satisfaction of the Sibisa application at the Medan City Population and Civil Registration Service Agency. 4) Simultaneous test results show that the variables of system quality, information quality and service quality have a significant effect on user satisfaction of the Sibisa application at the Medan City Population and Civil Registration Service Agency.